The influence of celebrity endorsement on college students' purchase intention towards cosmetics in Central China—An empirical study on Henan Province - Liang, Jiamei (2022)
The main objective of this paper is to explore the relationship between celebrity endorsements and college students' willingness to purchase cosmetics in central China, particularly in Henan Province. With the proliferation of celebrity endorsements, how companies choose the right endorsers to attract consumers intention to buy is an area of interest for scholars. However, most research on celebrity endorsement and purchase intentions has focused on Western countries, and there is a lack of research on the Chinese region. This paper fills the research gap by examining the relationship between celebrity endorsement and college students' willingness to purchase cosmetics in Henan Province, Central China. The study constructed a theoretical model using celebrity credibility, attractiveness, expertise, consistency and type as independent variables and purchase intention as dependent variables. Through an online data collection questionnaire, 315 valid data were obtained, and quantitative analysis was conducted using SPSS software. In Henan Province, China, the inclination of college students to purchase cosmetics is positively influenced by celebrity endorsement, according to the study's findings. And the results indicate that celebrity beauty, credibility, knowledge, and consistency between the celebrity and product might positively influence consumer purchase intentions, with celebrity credibility and consistency serving as the most influential criteria. This recommends that cosmetic companies in central China, particularly in the province of Henan, should utilize celebrity endorsements in their marketing campaigns. When picking spokespeople, companies and marketers look for celebrities with charisma, reliability, competence, and a degree of product compatibility. Two of these characteristics, crediblity and a high degree of product fit, should be prioritized because they are more likely to elicit a favorable purchase intent from consumers.